TINGKAT KOMPETENSI PROFESIONAL CALON GURU GEOGRAFI PRODI PENIDIKAN GEOGRAFI FMIPA UNM - Suprapta Suprapta (Seminar Nasional LP2M UNM, 2017)
Teacher candidate accordance with the development of learning techniques are always socialized in various occasions , it appears that future teachers in teaching and learning activities on the wane . This is because students are used as a central activity in the learning process. This study reveals Geography Teachers teaching experience,obstacle, and contribution to the professional competence . Teacher as facilitator demanded a lot of experience in the learning process in the same scientific field , and stability in the scientific field will be visible if the science that they do the same with the knowledge that has been gained during a student teacher candidates . As a result the ability of teachers is more stable and seems more mature teacher competence is determined by his experience is determined by other factors , so it deserves given systematic enrichment and training that will increase their competence and make teachers professional degree. Key words: teaching experience , obstacle, teacher competence